Pengaruh Inovasi Jam Kerja Pelayanan Malam (Jajanan Malam) Terhadap Kualitas Pelayanan Publik di Kantor Kelurahan Satimpo Kota Bontang - Sela Saputri; Heryono Susilo Utomo (Journal of Management and Social Sciences, 2024)
The need for the community to obtain quality public services requires the government to make many efforts to improve services in order to meet the expectations of citizens. Such as government efforts, namely by creating innovative services. One of them in the Satimpo Village, Bontang City, created an innovation in the working hours of night services "night snacks" which aims to improve public services related to village services. This study aims to determine how much influence the innovation of night service working hours (night snacks) has on the quality of public services at the Satimpo Village Office, Bontang City. The method in this study is quantitative with service innovation variables and public service quality variables. The data collection technique is using a questionnaire distributed to 99 respondents. Then analyzed using the SPSS 29 application. The results of the study stated that the coefficient of determination (R2) value was 0.301, which means that the influence of the innovation of night service working hours (night snacks) on the quality of public services at the Satimpo Village Office is 30.1% and the remaining 69.9% is influenced by other variables not examined in this study.